Study Protocol of the PreFiPS Study: Prevention of Postoperative Pancreatic Fistula by Somatostatin Compared With Octreotide, a Prospective Randomized Controlled Trial - Hain, Elisabeth; Challine, Alexandre; Tzedakis, Stylianos; Mare, Alexandru; Martinino, Alessandro; Fuks, David; Adham, Mustapha; Piessen, Guillaume; Regimbeau, Jean-Marc; Buc, Emmanuel; Barbier, Louise; Vaillant, Jean-Christophe; et al. (Frontiers in Medicine, 2021)
Background: Pancreatic fistula (PF), i.e. a failure of the pancreatic anastomosis or closure of the remnant pancreas after distal pancreatectomy is one of the most feared complications after pancreatic surgery. PF is also one of the most common complications after pancreatic surgery, occurring in about 30% of patients. Prevention of a PF is still a major challenge for surgeons, and various technical and pharmacological interventions have been investigated, with conflicting results. Pancreatic exocrine secretion has been proposed as one of the mechanism by which PF occurs. Pharmacological prevention using somatostatin or its analogues to inhibit pancreatic exocrine secretion has shown promising results. We can hypothesis that continuous intravenous infusion of somatostatin-14, the natural peptide hormone, associated with 10 to 50-time stronger affinity with all somatostatin receptor compared to somatostatin analogues, will be associated with an improved PF prevention. Methods: A French comparative randomized open multicentric study comparing somatostatin vs. octreotide in adult patients undergoing pancreaticoduodenectomy (PD) or distal pancreatectomy (DP) with or without splenectomy. Patients with neoadjuvant radiation therapy and/or neoadjuvant chemotherapy within 4 weeks before surgery are excluded from the study. The main objective of this study is to compare 90-day grade B or C postoperative PF as defined by the last ISGPF (International Study Group on Pancreatic Fistula) classification between patients who receive perioperative somatostatin and octreotide. Additionally, we analyse overall length of stay, readmission rate, cost effectiveness, and postoperative quality of life after pancreatic surgery in patients undergoing PD. Conclusion: The PreFiPS study aim to evaluate somatostatin vs octreotide for the prevention of postoperative PF.